2019
DOI: 10.1589/jpts.31.424
|View full text |Cite
|
Sign up to set email alerts
|

Modified feedback-control task for examining the relationship between sense of agency and motor control: a pilot study

Abstract: [Purpose] A sense of agency and feedback control may be related when the sensory feedback is attributed to the self; however, the relationship between sense of agency and movement disorders remains unclear. Although a feedback-control task might enable the examination of this relationship, it may be difficult for patients with movement disorders to complete this task. The present study modified the feedback-control task for future clinical research. [Participants and Methods] Twenty-four healthy adults partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Regarding the results of motor performance, the difference in movement errors between the SELF and OTHER conditions was observed in each experiment week. This result replicates that of the previous studies [15,16,32], suggesting that PA and PB correctly completed the movement tasks, just like the participants in their previous studies did. Although movement errors of PA were greater in the OTHER condition than those of PB, there were no obvious differences in movement errors across the second, fourth, and eighth weeks in the performances of PA and PB.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the results of motor performance, the difference in movement errors between the SELF and OTHER conditions was observed in each experiment week. This result replicates that of the previous studies [15,16,32], suggesting that PA and PB correctly completed the movement tasks, just like the participants in their previous studies did. Although movement errors of PA were greater in the OTHER condition than those of PB, there were no obvious differences in movement errors across the second, fourth, and eighth weeks in the performances of PA and PB.…”
Section: Discussionsupporting
confidence: 89%
“…To confirm whether PA and PB completed the movement task correctly, we compared movement errors between the SELF and OTHER conditions. In this task, the movement errors in the SELF condition should be smaller than those in the OTHER condition [15,16,32]. Since differences in movement errors across cycles were not of interest, the average movement error for each condition across cycles was calculated (Figure 3).…”
Section: Motor Performancementioning
confidence: 99%
“…While you are tracing the target line, you have to judge whether the cursor movement reflects your own or another's movement by referring to the spatiotemporal consistency between your actual movement and the cursor's movement." Our pilot study confirmed that healthy adults were capable of formulating correct self-other attributions of cursor movement (i.e., no significant misattributions were observed) by performing four cycles of the horizontal movement [35]. Before the main experiment, participants were trained to enable the horizontal movement of their upper limb without compensatory movements of the trunk.…”
Section: Plos Onesupporting
confidence: 65%